Microbiomes Detected by Bronchoalveolar Lavage Fluid Metagenomic Next-Generation Sequencing among HIV-Infected and Uninfected Patients with Pulmonary Infection - Yuting Tan; Zhong Chen; Ziwei Zeng; Songjie Wu; Jie Liu; Shi Zou; Min Wang; Ke Liang (Microbiology Spectrum, 2023)
ABSTRACT Comparison of lung microbiomes between HIV-infected and uninfected patients with pulmonary infection by metagenomic next-generation sequencing (mNGS) has not been described in China. The lung microbiomes detected in bronchoalveolar fluid (BALF) by mNGS among HIV-infected and uninfected patients with pulmonary infection were reviewed in the First Hospital of Changsha between January 2019 and June 2022. In total, 476 HIV-infected and 280 uninfected patients with pulmonary infection were enrolled. Compared with HIV-uninfected patients, the proportions of Mycobacterium (P = 0.011), fungi (P < 0.001), and viruses (P < 0.001) were significantly higher in HIV-infected patients. The higher positive rate of Mycobacterium tuberculosis (MTB; P = 0.018), higher positive rates of Pneumocystis jirovecii and Talaromyces marneffei (all P < 0.001), and higher positive rate of cytomegalovirus (P < 0.001) contributed to the increased proportions of Mycobacterium, fungi, and viruses among HIV-infected patients, respectively. The constituent ratios of Streptococcus pneumoniae (P = 0.007) and Tropheryma whipplei (P = 0.002) in the bacteria spectrum were significantly higher, while the constituent ratio of Klebsiella pneumoniae (P = 0.005) was significantly lower in HIV-infected patients than in HIV-uninfected patients. Compared with HIV-uninfected patients, the constituent ratios of P. jirovecii and T. marneffei (all P < 0.001) in the fungal spectrum were significantly higher, while the constituent ratios of Candida and Aspergillus (all P < 0.001) were significantly lower in HIV-infected patients. In comparison to HIV-infected patients without antiretroviral therapy (ART), the proportions of T. whipplei (P = 0.001), MTB (P = 0.024), P. jirovecii (P < 0.001), T. marneffei (P < 0.001), and cytomegalovirus (P = 0.008) were significantly lower in HIV-infected patients on ART. Significant differences in lung microbiomes exist between HIV-infected and uninfected patients with pulmonary infection, and ART influences the lung microbiomes among HIV-infected patients with pulmonary infection. IMPORTANCE A better understanding of lung microorganisms is conducive to early diagnosis and treatment and will improve the prognosis of HIV-infected patients with pulmonary infection. Currently, few studies have systematically described the spectrum of pulmonary infection among HIV-infected patients. This study is the first to provide comprehensive information on the lung microbiomes of HIV-infected patients with pulmonary infection (as assessed by more sensitive metagenomic next-generation sequencing of bronchoalveolar fluid) compared with those from HIV-uninfected patients, which could provide a reference for the etiology of pulmonary infection among HIV-infected patients.